Intrapancreatic Lesion of Biliary Duct Following a Blunt Trauma: A Rare Entity Difficult to Identify with Conservative Management - M Jiménez-Fuertes; J Ruiz-Tovar; M. Durán-Poveda; D García-Olmo (Open Journal of Trauma - Peertechz Publications, 2017)
Lesions of the biliary duct following a blunt abdominal trauma occurs infrequently, and even more so when it occurs in the intrapancreatic biliary duct. With the increase of conservative treatment in blunt abdominal trauma, the diagnosis of this entity can be difficult and delayed. We present the case of a lesion of the intrapancreatic biliary duct following a blunt trauma. A 51-year-old male patient was treated following a  bicycle accident. Initial CT scan showed multiple bilateral rib fractures and grade 2 liver injury in segment VII. On the basis of these findings and the stability of the patient, a conservative treatment was adopted. On the 9th day following admission he developed a progressive jaundice. This prompted a Doppler ultrasonography of the liver, showing no abnormalities in the pedicle or hepatic vessels, as well as an MR-cholangiography, which only revealed an increased amount of abdominal fl uid without dilatation of the bile duct and without apparent injury of the duct.Upon the onset of fever and general worsening of the patient's condition, an exploratory laparotomy was performed on the 16th day following admission, revealing plenty of intraperitoneal bile fl uid, but a visual examination of the bile duct failed to determine the site of injury. An intraoperative ERCP was performed, revealing a lesion of the intrapancreatic bile duct, after which a biliary stent was inserted.In the early postoperative period the patient developed a leak through the external biliary drains placed during laparotomy. A new ERCP was therefore performed, together with the insertion of a coated metal prosthesis, after which the patient progressed satisfactorily. Damage to the intrapancreatic bile duct by blunt abdominal trauma is a rare entity, diffi cult to diagnose  especially with the increase of conservative treatment of associated injury such as liver damage. MR  cholangiography and ERCP play a fundamental role in the diagnosis and actual endoscopic treatment of these injuries (with or without a surgical cavity wash) and, when feasible, this constitutes the best option for treatment.